Minimum meal frequency and associated factors among children aged 6–23 months in Sub-Saharan Africa: a multilevel analysis of the demographic and health survey data - Tebeje, Tsion Mulat; Abebe, Mesfin; Tesfaye, Solomon Hailemariam; Seboka, Binyam Tariku; Argaw, Girum Shibeshi; Seifu, Beminate Lemma; Mare, Kusse Urmale; Aragaw, Fantu Mamo (Frontiers in Public Health, 2024)
BackgroundWorldwide, approximately half of all children are not provided the minimum meal frequency (MMF). Sub-Saharan Africa (SSA) had the lowest proportion of children aged 6–23 months who met the requirements of the complementary feeding indicators, including MMF. Ensuring adequate meal frequency poses a challenge in numerous developing countries, particularly in regions characterized by low household food security, such as SSA. Therefore, this study aimed to assess the pooled prevalence of MMF and its associated factors in SSA via the most recent demographic and health survey data.MethodsA total of 100,526 weighted samples from demographic and health survey datasets of 35 SSA countries were used. A multilevel Poisson regression model with robust variance was applied to identify factors associated with MMF, and the model with the lowest deviance was the best-fitted model. An adjusted prevalence ratio with a 95% confidence interval (CI) was reported, and variables with a p < 0.05 were considered statistically significant.ResultsThe pooled prevalence of MMF among children aged 6–23 months in SSA was 38.47% (95% CI: 34.97–41.97), which ranged from 21.41% in Liberia to 63.98% in Madagascar. According to the subgroup analysis, the pooled magnitude of MMF in central, west, east, and southern Africa was 36.42, 35.46, 39.97, and 50.69%, respectively. Marital status, maternal education level, sex of household head, working status, wealth index, media exposure, age of the child, postnatal check-up, breastfeeding status, residence, and SSA regions were significantly associated with minimum meal frequency.ConclusionLess than forty percent of infants and young children in SSA receive the minimum recommended meal frequency, which is relatively low. This presents a notable difficulty in efforts to prevent malnutrition and attain sustainable development goals related to health and nutrition on the continent. Therefore, priority should be given to empowering women, promoting breastfeeding and postnatal check-ups, targeting infants who just started complementary feeding, and spreading information through media.